Anti-inflammatory, Anti-nociceptive and Toxicity Studies of Homoeopathic Formulation Rück-Pain™ Against Spondylitis (Advancements in Homeopathic Research, 2022)
Introduction: Spine-related problems are continuously increasing due to current lifestyle, environmental and genetic factors. Lifestyle factors like prolonged sitting, lack of exercise and wrong posturefurther aggravate these problems. A homoeopathic formulation Rück Pain™ was developed to treat the symptoms arising from spinal disorders and surrounding regions. Its ingredients are covered by homoeopathic pharmacopoeia (s) and authoritative literature. Objective: The current study aimed to evaluate the anti-inflammatory, anti-nociceptive and toxicity effects of Rück-Pain™ in mice animal model. Materials and methods: Swiss albino mice were divided into 6 groups viz. vehicle control, disease control, treatment dose 1 (2.96ml/kg), treatment dose 2 (6ml/kg), treatment dose 3 (8.80ml/kg) and standard treatment. Spondylitis was induced by the administration of Sodium thioglycolate 0.1ml (1% solution) at neck joint region of mice. Anti-inflammatory effect was evaluated by measuring erythrocyte sedimentation rate (ESR) and area of inflammation in volume in the neck region by Vernier caliper. Anti nociceptive effect was evaluated using tail-flick assay. Histological changes in liver and spleen were assessed to find out the toxicity by the treatment groups. Statistical analysis was done using one-way analysis of variance (ANOVA) considering P=
Keywords: homoeopathic; pharmacopoeia; Anti-inflammatory; (ANOVA); Anti-nociceptive